Annotated Checklist of Brazilian Ophioninae (Hymenoptera: Ichneumonidae) - Fernandes, Daniell Rodrigo Rodrigues; Onody, Helena Carolina; Lara, Rogéria Inês Rosa; Perioto, Nelson Wanderley (EntomoBrasilis, 2014)
The aim of this study was to provide an updated checklist of the species of Ophioninae reported for Brazil. Were catalogued 86 nominal species of Ophioninae, of which 61 of Enicospilus, nine of Thyreodon, five of Stauropoctonus, three of Ophiogastrella and of Ophion, two of Alophophion and of Rhynchophion and one of Prethophion. Enicospilus, to occur in 19 states and, is the most widely distributed genus. The present study reveals that knowledge of the fauna of Ophioninae is incipient in Brazil, much of the country remains subsampled and should have priority in future studies. Lista Anotada dos Ophioninae (Hymenoptera: Ichneumonidae) Brasileiros Resumo. O objetivo deste estudo foi apresentar uma lista atualizada das espécies de Ophioninae (Hymenoptera: Ichneumonidae) relatadas para o Brasil. Foram catalogadas 86 espécies, dentre as quais 61 de Enicospilus, nove de Thyreodon, cinco de Stauropoctonus, três de Ophiogastrella e de Ophion, duas de Alophophion e de Rhynchophion e uma de Prethophion. Enicospilus, por ocorrer em 19 estados, é o gênero com maior distribuição geográfica. O presente estudo revela que o conhecimento da fauna de Ophioninae no Brasil é incipiente, que grande parte do país continua subamostrada e deve ter prioridade em estudos futuros.